Research Progress of RNA Methylation Modification in Colorectal Cancer - Liang, Weizheng; Yi, Hongyang; Mao, Chenyu; Meng, Qingxue; Wu, Xueliang; Li, Shanliang; Xue, Jun (Frontiers in Pharmacology, 2022)
Accumulating evidence indicates that RNA methylation, as the most common modification of mRNA, is of great significance in tumor progression and metastasis. Colorectal cancer is a common malignant tumor of the digestive system that seriously affects the health of middle-aged and elderly people. Although there have been many studies on the biological mechanism of the occurrence and development of colorectal cancer, there are still major deficiencies in the diagnosis and prognosis of colorectal cancer. With the deep study of RNA methylation, it was found that RNA modification is highly related to colorectal cancer tumorigenesis, development and prognosis. Here, we will highlight various RNA chemical modifications including N6-methyladenosine, 5-methylcytosine, N1-methyladenosine, 7-methylguanine, pseudouridine and their modification enzymes followed by summarizing their functions in colorectal cancer.